1978
DOI: 10.1113/jphysiol.1978.sp012416
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium ions in transient inward currents and aftercontractions induced by strophanthidin in cardiac Purkinje fibres.

Abstract: 3. TI was closely associated with a phasic increase in force ('aftercontraction'). Like TI, the aftercontraction was evoked by a preceding action potential or by the break of a strong depolarizing pulse.4. TI and the aftercontraction displayed similar wave forms although peak current preceded peak force by 50-100 msec. Both transients were enhanced by increasing the strength or duration of the preceding depolarization pulse. Both events were slowed as the potential level following the pulse was displaced in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
310
7
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 628 publications
(349 citation statements)
references
References 44 publications
31
310
7
1
Order By: Relevance
“…In this study we examine the role of I Ca,L and sarcoplasmic reticulum (SR) Ca 2Ï© release in the action of PUFAs on cardiac myocytes. We observe clear reductions in I Ca,L and SR Ca 2Ï© release, both important in Ca 2Ï© overload arrhythmias (11)(12)(13)(14)(15). We find that the direct action of PUFAs responsible for the reduced SR Ca 2Ï© release is on I Ca,L .…”
mentioning
confidence: 62%
“…In this study we examine the role of I Ca,L and sarcoplasmic reticulum (SR) Ca 2Ï© release in the action of PUFAs on cardiac myocytes. We observe clear reductions in I Ca,L and SR Ca 2Ï© release, both important in Ca 2Ï© overload arrhythmias (11)(12)(13)(14)(15). We find that the direct action of PUFAs responsible for the reduced SR Ca 2Ï© release is on I Ca,L .…”
mentioning
confidence: 62%
“…Regarding pharmacological effects, several mechanisms have been proposed to explain the potential beneficial effect of magnesium in asthma. It has been shown to relax airway smooth muscle in vitro [2], probably by the modulation of calcium ion movement within the cell [20] and through transmembrane calcium channels [21,22], as well as to broncho;dilate asthmatic airways in vivo [4,5]. It has been demonstrated that histamine and methacholine PD20 threshold dose is moved to the right when the patients were pretreated with aerolized magnesium sulfate, with this effect considered to be similar than that observed with calcium channel blockers [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Far from being a passive repository of excess Ca 2+ ions, however, the Ca 2+ content within the SR ([Ca 2+ ] SR ) serves as a critical regulator of the release process itself. Dynamic decreases in local [Ca 2+ ] SR are thought to aid in terminating the elementary units of release, Ca 2+ sparks (Sobie et al, 2002;Terentyev et al, 2002), and, when SR Ca 2+ content is excessive, regenerative release of Ca 2+ is thought to produce arrhythmias (Lederer and Tsien, 1976;Kass et al, 1978;Berlin et al, 1989;Cheng et al, 1996). Here we discuss the balance of influx of Ca 2+ into the SR and its release through Ca 2+ sparks and Ca 2+ "leak".…”
Section: Introductionmentioning
confidence: 95%